Nursing of a patient with radiotherapy- and chemotherapy-induced adverse reactions treated with aruricualr acupoint pressing combined with meridian acupoint Tuina (耳穴贴压联合经穴推拿治疗放化疗后不良反应1例护理体会) - JIN Yi (金艺); MIN Tingyan (闵婷燕) (中西医结合护理)
This paper summarizes the nursing experience of a patient with radiotherapy- and chemotherapy-induced adverse reactions treated with aruricualr acupoint pressing combined with acupoint Tuina. After 1 week of outpatient chemo-radiotherapy, the patient developed various adverse effects including common problems including bone marrow suppression, nausea and loss of appetite. Based on the comprehensive nursing evaluation and the concept of Traditional Chinese Medicine syndrome differentiation and care, this case adopts the method of combining auricular acupoint pressing and meridian acupoint Tuina for intervention. After intervention, the patient was observed with less pain, relief of nausea and vomiting, improved sleep quality, relief of anxiety, and improved bone marrow function and nutritional status scores. This indicates that the combined Traditional Chinese Medicine nursing techniques can effectively alleviate the adverse reactions caused by radiotherapy and chemotherapy, thus significantly improving the quality of life of the patient. (本文总结耳穴贴压联合经穴推拿治疗1例放化疗后出现不良反应患者的护理经验。患者在门诊接受放化疗后出现了多种不良反应, 包括骨髓抑制、恶心和食欲不振等常见问题。基于全面的护理评估及中医辨证施护的理念, 采用耳穴贴压与经穴推拿相结合的方法进行干预。患者疼痛程度减轻, 恶心呕吐症状缓解, 睡眠质量提高, 焦虑情绪得到改善; 同时, 其骨髓功能恢复情况良好, 营养状况评分也有所提升。采用联合应用中医护理技术, 可以有效缓解放化疗相关不良反应, 对提高患者生活质量具有积极意义。)